2016
DOI: 10.1002/cphc.201600223
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Electronic Properties of the Dative N−B Bond with Associated O−B Interaction: Electron Localizability Indicator from X‐Ray Wavefunction Refinement

Abstract: Despite the immense growth in interest in difluoroborate dyes, the nature of the interactions of the boron atom within the N-BF2 -O kernel is not yet fully understood. Herein, a set of real-space bonding indicators is used to quantify the electronic characteristics of the dative N-B bond in difluoroborate derivatives. The atoms-in-molecules (AIM) partitioning scheme is complemented by the electron localizability indicator (ELI-D) approach, and both were applied to experimental and theoretical electron-density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
(80 reference statements)
2
7
0
Order By: Relevance
“…The derived B–N bond QTAIM properties (see Table ) can also be confronted with the ones already reported in the literature. Both in our previous work, and in the works by Mebs et al , and Chęcińska et al, the experimentally derived electron density values are very much comparable to the results determined in the current study, and they range from 0.76 to 1.08 e·Å –3 . More peculiar behavior is observed for the Laplacian.…”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The derived B–N bond QTAIM properties (see Table ) can also be confronted with the ones already reported in the literature. Both in our previous work, and in the works by Mebs et al , and Chęcińska et al, the experimentally derived electron density values are very much comparable to the results determined in the current study, and they range from 0.76 to 1.08 e·Å –3 . More peculiar behavior is observed for the Laplacian.…”
Section: Results and Discussionsupporting
confidence: 91%
“…In our previous work, devoted to a model arylboronic azaester crystal, the determined Laplacian was equal to −4.36(8) e·Å –5 , which has an opposite sign to the one determined in this contribution. On the other hand, in the majority of studies, as reported by other groups, the Laplacian exhibits a positive sign. This can be explained by the change of the B–N interaction character across many complexes and bonding distances, as described by us in details .…”
Section: Results and Discussionmentioning
confidence: 83%
“…Working in this sense, Kohout have proposed the Electron Localizability Indicator (ELI–D) [14,15] which is based on the motion of same spin electron density. ELI–D is an useful tool for the detection of chemical bonding signatures in molecule or crystal [16,17] . The combination of AIM and ELI–D approaches is also an issue to determine the Raub‐Jansen Index (RJI) [18,19] which is an appropriate tool to describe the bond polarity.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray restrained wavefunctions have been used in diverse studies for the analysis of crystal interactions and properties, e.g. for refractive indices [19,20] or for the study of bonds [21][22][23][24][25] , etc. While the majority of XRW studies focused on the electron density and its related properties in crystals, the XRW technique also provides molecular orbitals that were successfully used, for example, in the study of hypervalency [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%